65.4k views
21 votes
Convert the equation to vertex form.
y = x2 – 8x + 10

User Falomir
by
5.3k points

2 Answers

6 votes

Answer:

y = (x - 4)² - 6

Explanation:

use the 'completing the square' method:

x² - 8x + 10 = 0

x² - 8x + 16 = -10 + 16

(x - 4)² = 6

y = (x - 4)² - 6

User Brozorec
by
5.2k points
9 votes

Answer:

Explanation:

y = (x² - 8x) + 10

Complete the square

 coefficient of the x term: -8

 divide it in half: -4

 square it: (-4)² = 4²

 use 4² to complete the square and keep the equation balanced:

y = (x²-8x + 4²) - 4² + 10

y = (x-4)² - 6

User Mekazu
by
5.5k points